Vocal imitation between mothers and their children with cochlear implants. (16th August 2020) - Kondaurova, Maria V.; Fagan, Mary K.; Zheng, Qi
Abstract: To better explain variation in language acquisition in children with hearing loss, this study examined vocal (e.g., vocalization) and lexical (e.g., word) imitation in spontaneous interactions between mothers and children with 12 months of hearing experience using their cochlear implants ( n  = 12; mean age 27.9 months). Hearing children in two control groups were matched to children with cochlear implants, either by child chronological age ( n  = 12; mean age = 27.4 months) or by child hearing experience ( n  = 12; mean age 12 months). All three groups of mother–child dyads were audio‐recorded playing together. Mothers and children in all groups imitated their partners' vocalization and word utterances; however, the cochlear implant and hearing experience‐matched groups produced fewer word imitations than the age‐matched group. The frequency of preceding child vocalization or word production predicted maternal imitation type (vocalization or word); however, frequency of maternal vocalization predicted child vocalization imitation only. The results showed that child hearing experience affected imitation in both communication partners.